Tinjauan terhadap pelaksanaan Kem Bestari Solat - Asmawati Suhid,; Lukman Abdul Mutalib, (2009)
The main objective of Islamic Education is to strengthen the aqidah (beliefs) of Muslim pupils in schools. Furthermore, the Islamic Education Philosophy is formed according to oneness to Allah. Thus, the effort to strengthen and protect pupils’ aqidah can be seen in the curriculum and co-curricular activities of Islamic Education. Some of the aspects being emphasized are performing the five time prayers (solat). Performing prayers (solat) is the foundation or the pillar of Islam and practicing it reflects the submission and obedience to Allah. The introduction of the Smart Prayer Camp activity through the j-QAF Programme is the latest approach aimed at educating and encouraging pupils to perform prayers in their daily lives. Since the Smart Prayer Camp was recently introduced, a study was carried out to identify the effectiveness of its implementation. A total of 309 j-QAF teachers in Selangor were involved in this research. The quantitative data gathered were analysed using the Statistical Package for the Social Sciences (SPSS) programme. In general, the findings have shown that these pupils were interested to participate in the Smart Prayer Camp. This paper is also meant to examine issues faced in the implementation of the Smart Prayer Camp, and thus several recommendations are presented in this paper.